Letter (copy) : Save the Basque Children Fund - Citrine, Walter, 1887-1983
037-0049-001 WMC/LK/703 Finance 15th September, 1937. Mr. W. Brown, Secretary, Aberdeen Trades Council, 47, Belmont Street, ABERDEEN. Dear Mr. Brown, "Save the Basque Children Fund". In reply to your letter of the 13th instant, I regret to say that after a thorough search I am unable to trace having received your Money-Order value £10., which you state was forwarded to this office on 3rd August last. I can only suggest, however, that you get in touch with the Postal Authorities as soon as you are able. Yours sincerely, General Secretary. 292/946/37/49